THE ANALYSIS OF STUDENTS' DIFFICULTIES IN LEARNING ENGLISH USING CAMBRIDGE CURRICULUM : students' difficulties, English learning, Cambridge Curriculum - Ananda Nurkholis; Lisan, Khusnul Harsul (English Education Study Program STKIP PGRI Pacitan, 2025)
This research aimed to analyze students' difficulties in learning English using Cambridge Curriculum. Furthermore, the research tried to look for solutions from the obstacles. The research used a qualitative method with a case study approach. The stages of the research included initial research and data collection, transcription of conversations and interview results, conducting data analysis, and the reports. Data collection techniques in this study were observation, interviews, and documentation, with research subjects consisting of 10 students from eight-grade MTs students, one English teacher, and a representative from Assalafiyah Language Center (ALC) who oversaw the implementation of the Cambridge Curriculum at MTs Assalafiyah. To analyze the data, this research used Miles and Huberman’s theory. It consisted of data collection, data reduction, data display, and conclusion drawing/verification. The results showed that there were obstacles experienced by the students related to learn English using Cambridge Curriculum, such as limited mastery of vocabulary, which made it difficult for students to understand the explanations in the book. This was also the cause of students' lack of understanding when the teacher explained the material using full English and due to limited time in the learning process. The alternative solution for students was to start memorizing vocabulary and practice it in everyday life. Thus, teachers were expected to mix English and Indonesian language when explaining the material and add time for lesson hours so that students could learn optimally to maximize the implementation of the Cambridge curriculum in MTs Assalafiyah.